LSS och utlandsresor- Rättigheter och rättsdogmatik i konflikt? - Sandberg,Carl Martin (2024)
In this essay, the legal situation regarding the possibility of receiving assistance for traveling abroad, for the LSS (Law on Support and Service for Persons with Certain Functional Impairments) target group, is examined. The investigation is carried out using both a legal realist dogmatics method and a social legal dogmatics approach. The conclusion is that the right to assistance with vacation trips is reserved for those with the greatest support needs. These support needs must be of a constant nature and can not arise solely as a consequence of dealing with a new environment while travelling, to be legally relevant. In Sweden, the municipalities are responsible for implementing the LSS in reality, even though there is a possibility to engage private actors. In cases where the need for personal assistance exceeds 20 hours per week on average, the Swedish Social Insurance Agency is responsible for financing according to the Assistance Allowance Act. The UN has expressed concerns regarding differences between regions and municipalities, regarding the interpretation of the LSS. At the same time, there are issues with the wording of LSS, that have also been pointed out by a recent (2024) UN report. LSS is still a legislation that relies more on medical assessments than social needs. This has also been criticized by the UN. The opportunity of traveling abroad to a destination one has personally chosen and dreamed of, during one’s lifetime, clearly falls under the concept of “good living conditions.” To ensure that this opportunity is not dependent on civil society or family, it is likely that the LSS needs to be completely revised. The question of LSS and travelling lies at the intersection of law and politics. It has been shown that the Swedish Administrative Supreme Court (HFD) has been reluctant to enforce distributive justice in unclear cases, especially when it comes to obliging municipalities to carry out activities abroad. This would probably require legislative measures. It may be argued that it would not be appropriate for the HFD to ”take the driver’s seat” through expanding social rights, as the court should not be political in its judgements. Ultimately, the issue at stake is to what extent social rights can be limited due to budgetary considerations. One possible way forward is to protect these rights constitutionally. The essay highlights the difference between how the social legal doctrine and even the United Nations views the LSS as a rights legislatation, and how Swedish courts apply the LSS.
Keywords: socialrätt; förvaltningsrätt; LSS